2013
DOI: 10.1002/jcu.22071
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound versus palpation guidance for intra‐articular injections in patients with degenerative osteoarthritis of the elbow

Abstract: US-guided IA elbow injections by posterior approach may raise the accuracy rate in elbow joint injections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Intra-articular contrast agent injection prior to CT-arthrography should always be performed with an imaging-guided technique rather than a palpation-guided technique, since it results in more accurate intra-articular delivery, as confirmed by Kim et al [ 38 ].…”
Section: The Role Of Ct-arthrographymentioning
confidence: 99%
“…Intra-articular contrast agent injection prior to CT-arthrography should always be performed with an imaging-guided technique rather than a palpation-guided technique, since it results in more accurate intra-articular delivery, as confirmed by Kim et al [ 38 ].…”
Section: The Role Of Ct-arthrographymentioning
confidence: 99%
“…Despite the successful results of non-image-guided intra-articular hip injections in several studies described above, previous studies have demonstrated significantly improved accuracy, pain, and/or functional outcomes for image-guided versus palpation-guided injections of the knee joint [ 2 ], acromioclavicular joint [ 22 , 23 ], distal radioulnar joint [ 24 ], elbow joint [ 25 ], subacromial space [ 26 ], and the peroneal tendon sheath [ 27 ]. However, as mentioned above, image-guided injections come with an increased cost to patients and time lost between presentation and established diagnosis, two important parameters that the current technique aims to address.…”
Section: Discussionmentioning
confidence: 99%
“…( 5 ) and Kim et al . ( 6 ) reported higher accuracy rates for the US-guided (91% and 100%, respectively) versus landmark-guided (64% and 77.5%, respectively) injection approaches.…”
Section: Elbowmentioning
confidence: 98%